Management of Mallet Fracture by Closed Extension-Block Pinning – A case based review of a novel technique - Agarwal, Sharat (Electron Physician, 2013)
Close reduction by extension-block K-wire fixation for acute mallet fracture is a relatively novel mode of treatment which is based on two sound orthopedic principles – stable arc splinting and early protected motion. Distal interphalangeal joint splinting is still the technique commonly used for mallet fractures with significant morbidity and only moderate functional outcome. We have demonstrated here Ishiguro’s technique in a partially treated 2 weeks old mallet fracture with the flexion deformity at distal interphalangeal (DIP) joint after proper preoperative assessment. Peroperatively, proper anatomical localization of mallet fragment was done under fluoroscopy. Reduction of the avulsion fracture was done by extension block K-wire and intra-articular K-wire was inserted subsequently to hold the reduction in place and DIP joint in extension. Later on K-wires were removed at the end of 6 weeks follow up. Patient was subjected to the physiotherapy during the course of the treatment. Excellent functional outcome was noted at the end of three months.